Pengaruh Dominasi Kelompok Santri dalam Dinamika Pemerintahan Desa (Studi Kasus di Desa Wringinrejo Kabupaten Mojokerto) - Ryan, Jacko (Sawala : Jurnal pengabdian Masyarakat Pembangunan Sosial, Desa dan Masyarakat, 2020)
Life in the village was always closely linked to cultural and religious elements. Both of these aspects get an impact on the activity that occurs in the villages, most of which is the activity of government. Therefore, this research explored the heterogeneity of religious-cultural groups in rural communities and their impact on village governance dynamics. This research was conducted by a qualitative descriptive method in the village of Wringinrejo, Mojokerto Regency. Through this research, the theory of the Javanese Religion invented by Clifford Geertz was found irrelevant. This is indicated by the convergence between the Santri the Abangan groups and the acculturation of culture and religion in the Village of Wringinrejo. The results of this research showed that the governance dynamics of the Wringinrejo Village were dominated by the Santri group. A variety of political activities also were performed by the Santri group and have influenced various policies in the village.